Cross-cultural Adaptation and Psychometric Properties of the Arabic Version of the Academic Nurse Self-Efficacy Scale - Bajet, Junel Bryan Arre; Cruz, Jonas Preposi; Balay-odao, Ejercito Mangawa; Mesde, Jennifer; Alquwez, Nahed; Alotaibi, Khalaf; Cacanando, Sheerween (Makara Journal of Health Research, 2023)
Background: Students’ academic self-efficacy is greatly associated with their academic performance. An effective instrument is needed to assess academic self-efficacy in the Saudi context. This study assessed the psychometric properties of the Academic Nurse Self-Efficacy Scale-Arabic version (ANSE-A) given to student nurses and the associations between the students’ demographics and overall ANSE-A scores. Methods: Quantitative and descriptive methods were applied. The study was conducted from January to July 2022 at Shaqra University with 200 nursing students as the convenience sample. For content validity, the item-level content and scale-level content validity indices were utilized following the averaging method. We used Cronbach’s alpha (α) to measure the reliability. Meanwhile, for construct validity, we performed an analysis of the principal component with varimax rotation and applied a t-test and ANOVA for the tests of the association of variables. Results: Four distinct factors were revealed in the factor analysis, and they explained 64.86% of the variance. The 14-item ANSE-A’s overall Cronbach’s alpha was 0.87, with four factors ranging from 0.74 to 0.76. The academic self-efficacy of the students was found to be associated with their gender and GPA. A weak positive correlation existed between the students’ GPA and academic self-efficacy (r = 0.17, p = 0.017). Conclusions: The ANSE-A is a valid and reliable instrument that can be utilized to assess the academic self-efficacy of student nurses in Saudi Arabia. The results of the assessment may be used to help boost nursing students’ achievement and emotional health and serve as a valid predictor of motivation and learning.